2020
DOI: 10.1186/s12933-020-01100-w
|View full text |Cite
|
Sign up to set email alerts
|

Metformin treatment in heart failure with preserved ejection fraction: a systematic review and meta-regression analysis

Abstract: Background: Observational series suggest a mortality benefit from metformin in the heart failure (HF) population. However, the benefit of metformin in HF with preserved ejection fraction (HFpEF) has yet to be explored. We performed a systematic review and meta-analysis to identify whether variation in EF impacts mortality outcomes in HF patients treated with metformin. Methods: MEDLINE and EMBASE were searched up to October 2019. Observational studies and randomised trials reporting mortality in HF patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 48 publications
0
26
0
2
Order By: Relevance
“…In HFpEF patients, metformin reduced long-term mortality following admission for acute HF and all-cause mortality in subjects with poor glycemic control [ 193 , 194 ]. A recent systematic review and meta-regression analysis confirmed a significant reduction of mortality in HFpEF by metformin, even after adjustment for HF therapies including β-blockers and angiotensin II inhibitor ACE-Is [ 195 ].…”
Section: Effects Of Metformin On Adverse Consequences Of Hf In Clinical Studiesmentioning
confidence: 99%
“…In HFpEF patients, metformin reduced long-term mortality following admission for acute HF and all-cause mortality in subjects with poor glycemic control [ 193 , 194 ]. A recent systematic review and meta-regression analysis confirmed a significant reduction of mortality in HFpEF by metformin, even after adjustment for HF therapies including β-blockers and angiotensin II inhibitor ACE-Is [ 195 ].…”
Section: Effects Of Metformin On Adverse Consequences Of Hf In Clinical Studiesmentioning
confidence: 99%
“…Several trials and meta-analyses have established that metformin, the only publicly available biguanide, is safe, efficacious, and is associated with improved cardiovascular outcomes in heart failure patients, making metformin first-line therapy for the treatment of DM in HFpEF patients [35][36][37][38]. A recent systematic review and meta-regression analysis suggest that the use of metformin in patients with HFpEF is associated with reduced mortality in HFpEF and HFrEF after adjustment for heart failure therapies such as angiotensin converting enzymes inhibitors (ACEI) and beta-blockers (BB).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Лишь при применении метформина в лечении пациентов с сочетанием СД и ХСН (в т.ч. и с сохраненной ФВ ЛЖ) отмечалось снижение риска смерти [20,21]. У некоторых антидиабетических препаратов было выявлено даже негативное влияние на сердечно-сосудистые исходы.…”
Section: эпидемиология и патогенетическиеunclassified